An isotopic overview of dietary habits and subsistence practices in the Aegean World - Irvine, Benjamin (Frontiers in Environmental Archaeology, 2025)
This study provides a broad overview of human dietary habits and subsistence practices across time in the Aegean World (defined in the East by the coastal littoral of western Anatolia, Crete to the South, and eastern mainland Greece in the West). This was done principally through the collation and examination of previously published stable carbon and nitrogen isotope ratios (δ13C and δ15N values) from human bulk bone collagen. The sites/populations examined in this study date from the Neolithic to the Late Byzantine periods; ca. 6000 BC to the early 16th century AD. Broadly speaking, the stable isotope values demonstrate general consistency diachronically, although a slight and gradual increase in δ13C values over time is observed. The δ15N values are also broadly similar diachronically, with the exception of the Classical (and to a lesser extent Hellenistic and Byzantine) periods which have noticeably higher δ15N values than the preceding and following periods. Interestingly, and perhaps unexpectedly, there are no clearly observable differences between the sub-regions of the Aegean World (i.e., East Aegean, Crete, West Aegean). The observed findings would, therefore, suggest broadly similar dietary habits and subsistence practices in the Aegean World from the Neolithic period onwards, perhaps pointing toward dietary habits and subsistence practices being a further facet of connectivity in the region.